Energy-capital-labor substitution and the economic effects of CO 2 abatement: Evidence for Germany - Claudia Kemfert; Heinz Welsch (Fondazione Eni Enrico Mattei (FEEM), 1998)
Although the economic effects of CO2 abatement depend substantially on the degree to which capital and labor can substitute for energy, the issue of energy-capital-labor substitution is surrounded by considerable uncertainty. In this paper we use econometrically estimated, sectorally differentiated elasticities of substitution for Germany to shed some light on this issue. The elasticity estimates are used within a dynamic multi-sector CGE model to assess the economic effects of CO2 emission limits for Germany. In particular, we consider the implementation of emission limits by means of a carbon tax, assuming two alternative ways of tax revenue recycling, i.e. lump-sum transfer to private households vs. labor cost reduction. The results are compared with results based on 'standard' substitution elasticities from the literature. Since the estimated elasticities are on average higher and closer to unity than the 'standard' elasticities, we get lower tax rates and tax revenues, and a more stable revenue/GDP ratio. In the case of using the tax revenue to reduce labor costs, the smaller revenue translates into a less favorable (but still positive) effect on employment and GDP. If the revenue is transferred to private households, the sensitivity of GDP with respect to the elasticities is rather negligible, whereas its various components are affected somewhat stronger.
Keywords: C5; D5; Q2; 330; Substitution elasticities; CO2 tax; General Equilibrium model; Luftreinhaltung; Treibhausgas-Emissionen; Ökosteuer; Steuerreform; Steuerwirkung; Energiesubstitution; Faktorsubstitution; Deutschland